HEPATITIS B SEROPOSITIVITY AMONG CHRONIC LIVER DISEASE PATIENTS IN HAZARA DIVISION PAKISTAN - Khan, Taher Salim; Rizvi, Farhat (Journal of Ayub Medical College Abbottabad, 2003)
Background: Hepatitis B virus infection is one of the major health problems in the developing countries including Pakistan. The present study was conducted to document the frequency of Hepatitis B seropositivity in patients with chronic liver disease in the Hazara Division. Methods: Serum samples were collected form 893 patients suffering from chronic liver disease (CLD) from all parts of the Hazara Division during period July 2000 to July 2002. Hepatitis HBsAg was detected by the immunochromatographic method. Results: A total of 271 (30.35%) tested positive for HBsAg including 199 males (73.43%) and 72 females (26.56%). Conclusion: There is a high frequency of HBV seropositive individuals of both sexes among patients referred for chronic liver disease. These frequencies obtained for Hazara Division compare well with figures from other parts of Pakistan as well as developing countries. Keywords: Hepatitis B, Chronic Liver Disease, HBsAg